Perilaku Pencarian Informasi Menurut Krikelas - Elsa Annisa Batu Bara; Kartika Amelia Nasution; Rafika Zahara Ginting; Novita Sari; Franindya Purwaningtyas (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
Everyone needs information that is accurate, relevant, fast and easy to obtain. Needs are defined as something that must be owned by someone who must be fulfilled. Everyone needs information that is accurate, relevant, fast and easy to obtain. Needs are defined as something that must be owned by someone who must be fulfilled. Everyone can fulfill information needs, they will search for information through information sources, a number of behaviors shown by them in searching for information are referred to as information seeking behavior. Information seeking behavior is an activity in determining and identifying messages to satisfy the perceived information needs. The purpose of writing this article is to find out about information seeking behavior according to the criteria. Keywords: Library, Information Search, Cricket